Computed tomography volumetric analysis of frontal sinus pneumatization and its effect on lateral lamella angle - Alrehaili, Mona; Alharbi, Sara T.; Alharbi, Omar Ali A.; Alluhaybi, Bandar (Surgical and radiologic anatomy (English ed.), 2024)
Purpose Anatomical associations between the frontal sinus and anterior skull base must be carefully understood in preoperative imaging to minimize surgical complications. This study aims to investigate the relationship between frontal sinus volume and lateral lamella angle. Methods 150 computed tomography scans of paranasal sinuses (300 sides) were retrospectively reviewed. Pneumatization patterns were classified according to volume using a three-dimensional reconstruction analysis of the frontal sinuses. The angle formed between the lateral lamella and the horizontal plane in continuation with the cribriform plate was measured and grouped according to Gera classification based on the hypothetical risk of iatrogenic injury. Analysis of these measurements was conducted. Results A positive correlation was found between frontal sinus volume and lateral lamella angle. Hyperplastic frontal sinuses were the most prevalent followed by middle-sized sinuses. 5% of the frontal sinuses were aplastic. Lateral lamella angles ranging from 45 to 80 degrees (Gera class II) were the most common. Aplastic and hypoplastic frontal sinuses were common in subjects with less than 45 degrees lateral lamella angles (Gera class III). Males had significantly higher frontal sinus volumes and lateral lamella angles than females, while the influence of age was insignificant. Lateral lamella angles were significantly higher on the left side. Conclusion The frontal sinus volume affects the lateral lamella angle. Larger frontal sinuses are associated with higher lateral lamella angles and vice versa. Understanding this anatomical relationship can help prevent surgical complications.